Ultrasound irradiation as an effective tool in synthesis of the slag-based catalysts for carboxymethylation - Ekaterina Kholkina; Narendra Kumar; Kari Eränen; Markus Peurla; Heikki Palonen; Jarno Salonen; Juha Lehtonen; Dmitry Yu. Murzin (Ultrasonics Sonochemistry, 2021)
Waste minimization strategy was applied in the current work for synthesis of the catalysts from industrial solid waste, namely desulfurization slag. The starting slag material comprising CaCO3, Ca(OH)2, SiO2, Al2O3, Fe2O3, and TiO2 was processed by various treating agents systematically varying the synthesis parameters. A novel efficient technique – ultrasound irradiation, was applied as an additional synthesis step for intensification of the slag dissolution and crystallization of the new phases. Physico-chemical properties of the starting materials and synthesized catalysts were evaluated by several analytical techniques. Treatment of the industrial slag possessing initially poor crystal morphology and a low surface area (6 m2/g) resulted in formation of highly-crystalline catalysts with well-developed structural properties. Surface area was increased up to 49 m2/g. High basicity of the neat slag as well as materials synthesized on its basis makes possible application of these materials in the reactions requiring basic active sites. Catalytic performance of the synthesized catalysts was elucidated in the synthesis of carbonate esters by carboxymethylation of cinnamyl alcohol with dimethyl carbonate carried out at 150 °C in a batch mode. Ultrasonication of the slag had a positive effect on the catalytic activity. Synthesized catalysts while exhibiting similar selectivity to the desired product (ca. 84%), demonstrated a trend of activity increase for materials prepared using ultrasonication pretreatment. The choice of the treating agent also played an important role in the catalytic performance. The highest selectivity to the desired cinnamyl methyl carbonate (88%) together with the highest activity (TOF35 = 3.89*10−7 (mol/g*s)) was achieved over the material synthesized using 0.6 M NaOH solution as the treating agent with the ultrasound pre-treatment at 80 W for 4 h.